Zones of Tradition - Places of Identity Cities and Their Heritage - Vinken, Gerhard (Urban Studies, 2021)
What is the heritage of our cities? Which are the monuments, places, and spaces in which it accumulates, and by which practices is it formed, handed down, appropriated? Gerhard Vinken takes the readers to twelve cities on three continents and analyses the diverse and contradictory heritage formations that have had a lasting impact on urban life. The vitality of urban heritage, as these vivid and in-depth case studies show, lies in the dynamic and often conflictual processes of social appropriation and interpretation. Covering a diverse range of themes, the book familiarizes the reader with important questions and theories in urban research and heritage studies.